2019
DOI: 10.1016/j.appet.2019.104368
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of associations between the FTO rs9939609 genotype, fasting and postprandial appetite-related hormones and perceived appetite in healthy men and women

Abstract: Background: The fat mass and obesity-associated gene (FTO) rs9939609 A-allele has been associated with obesity risk. Although the exact mechanisms involved remain unknown, the FTO rs9939609 A-allele has been associated with an impaired postprandial suppression of appetite. Objectives: To explore the influence of FTO rs9939609 genotype on fasting and postprandial appetite-related hormones and perceived appetite in a heterogeneous sample of men and women. Design: 112 healthy men and women aged 18-50-years-old co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…For our participants who had severe obesity but were otherwise clinically healthy, it was difficult from meal test data to compare capacities for insulin secretion when blood glucose levels were as expected in subjects without diabetes. Our results are thus in line with those of Goltz et al [48]. They used a test meal with a higher energy and carbohydrate content than ours, yet did not detect obvious genotype effects from FTO rs9939609 on postprandial glucose and insulin responses.…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…For our participants who had severe obesity but were otherwise clinically healthy, it was difficult from meal test data to compare capacities for insulin secretion when blood glucose levels were as expected in subjects without diabetes. Our results are thus in line with those of Goltz et al [48]. They used a test meal with a higher energy and carbohydrate content than ours, yet did not detect obvious genotype effects from FTO rs9939609 on postprandial glucose and insulin responses.…”
Section: Plos Onesupporting
confidence: 93%
“…While most human studies examining the effect of the FTO rs9939609 risk allele on glucose tolerance and IS have assessed only fasting glucose and insulin levels, few have measured postprandial glucose and insulin responses [10,49,50]. To our knowledge, only one study has assessed postprandial blood glucose and insulin responses to a real life-mimicking meal [48], while no studies have assessed the association between the FTO risk allele and EGP in vivo. There are strengths and limitations to our study.…”
Section: Plos Onementioning
confidence: 99%
“…It has been proposed that the AA allele might alter the suppression of postprandial appetite, increasing the preference for high-calorie dense foods, stimulating hyperphagia and modulating satiety in the hypothalamus [6,10]. Nevertheless, there is still controversy to this proposal because other authors have not found any significant differences in the regulation of appetite of the FTO rs9939609 gene [11]; therefore, other physiological explanations should be searched for. One physiological mechanism in which the FTO rs9939609 gene could modulate fat mass is through the alteration of energetic metabolism and fat oxidation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…We performed a pooled analysis of data collected across two separate experimental studies; a cross-sectional study [ 26 ] and an acute cross-over study [ 27 ] conducted at Loughborough University. Both studies were conducted in the same laboratory, used identical protocols/ Standard Operating Procedures, and analytical approaches.…”
Section: Methodsmentioning
confidence: 99%